Development and performance assessment of a novel solar-assisted multigenerational system using high temperature phase change material. (22nd July 2022) - Khan, Muhammad Sajid; Mubeen, Ishrat; Jingyi, Wang; Zhang, Yan; Zhu, Gaojun; Yan, Mi
Abstract: Solar-assisted multi-generation systems are eco-friendly with exceptional thermal performance. In the present study, a novel solar-assisted multi-generational system is proposed and investigated for multiple outputs. The proposed system consists of solar tower with heliostat, combined cycle (topping is Brayton cycle, while bottoming is Rankine cycle with reheat and regeneration processes), single effect Lithium-Bromide/water absorption chiller, heat pump, water-based thermal energy storage system and an electrolyzer. The system is integrated with high temperature phase change material (PCM) based thermal storage system for the continuous system operation. The salt PCM KF-MgF2 is selected from the literature having melting temperature of 1280 K with high density and latent heat of fusion. The storage system ensures the stable and continuous working of the system during off sun hours. The aim of the present study is to thermodynamically and exergo-environmentally investigate the performance of PCM based solar driven multi-generation system. The results of the study depict that energy efficiency of single and multi-generation system is approximately 20.93% and 51.62%, while exergy efficiency is almost 22.51% and 53.45%, respectively. Hydrogen production rate and exergetic sustainability index of the proposed system is approximately 0.00742 kg/s and 0.078, respectively. Energy efficiency of multigeneration system is approximately 15.9% and 61% higher than tri-generation and co-generation systems at concentration ratio of 1000. Exergo-environmental impact index decreases to almost 5% by increasing direct normal irradiation, while exergetic sustainability index and exergy stability factor are increased to 125% and 54.2%, accordingly. Finally, energy efficiency of the single generation and multi generation systems are optimized at 23.56% and 56.83%, respectively. Graphical abstract: Image 1 Highlights: Thermodynamic analysis of PCM based solar assisted multigeneration system. Energy and exergy efficiencies of system are 51.62% and 53.45%, respectively. Energy efficiency of multigeneration is and 61% more than co-generation system. Exergetic sustainability index of integrated system is 0.078 respectively. Thermal efficiency of multi-generation system is optimized at 56.83%.